Genomic and phylotypic properties of three novel marine Bacteroidota from bare tidal flats reveal insights into their potential of polysaccharide metabolism - Ma, Kuo-Jian; Ye, Yong-Lian; Fu, Yun-Han; Fu, Ge-Yi; Sun, Cong; Xu, Xue-Wei (Frontiers in Marine Science, 2023)
Special geographical location and abundant organic matter profiles in tidal flats have resulted in great microbial diversity, in which Bacteroidota strains are considered as one of the primary degraders of polysaccharides, playing a crucial role in the carbon cycle. In this study, we collected sediment or sand samples from 34 bare tidal flats in China and investigated the profile of culturable bacteria, selected three Bacteroidota for polyphasic taxonomic analysis and revealed their polysaccharide metabolic potential. Totally, we isolated 352 pure cultured bacteria and they mainly distributed in Bacteroidota, Pseudomonadota, Bacillota, and Actinomycetota. It is shown that the bare tidal flats contained a large number of potential novel species, mainly distributed in Flavobacteriales and Cytophagales within Bacteroidota. Three Bacteroidota strains, M17T, M82T, and M415T, isolated from mudflat were selected for polyphasic taxonomic analysis. The 16S rRNA gene sequence similarity between strain M17T and Mangrovivirga cuniculi KCTC 72349T was 99.28%, and less than 90.09% with other species; strain M82T shared the highest 16S rRNA gene sequence similarity of 97.85% with Pontibacter litorisediminis KCTC 52252T, and less than 97.43% with other species; strain M415T had higher 16S rRNA gene sequence similarities with type species of genera Eudoraea (92.62-93.68%), Zeaxanthinibacter (92.02-92.91%), and Muriicola (92.21-92.83%). Phylogenetic analysis based on 16S rRNA gene sequences and single-copy orthologous clusters showed that strains M17T and M82T represent novel species within the genus Mangrovivirga and Pontibacter, respectively, and strain M415T represents a novel species of a novel genus within the family Flavobacteriaceae. The potential in polysaccharide metabolism of all these three strains was analyzed by genomes. The analysis revealed that glycoside hydrolases and glycosyltransferases account for more than 70% of the total CAZymes. Additionally, the numbers of polysaccharide utilization loci (PULs) and annotated CAZymes in Cytophagales spp. M17T and M82T were found to be higher than those in Flavobacteriales sp. M415T. Highly specialized saccharolytic systems and the presence of numerous diversified CAZymes for obtaining energy through polysaccharide metabolism were speculated to help the three novel strains adapt to the utilization of both terrestrial and marine polysaccharides.